Legal justification of free will as an absolute right - Savchenko, VO (Taras Shevchenko National University of Kyiv, 2022)
The article provides a legal justification for the absoluteness of free will. The understanding of free will has changed from imagining it as "fatum" in determinism to defining its limitations through international and national legal norms. Suppose the ancient philosophers wrote that God influences a person's will today. In that case, it is considered relevant to understand the limits of free will through the prism of regulatory and legal regulation. This thesis raises the pressing question of whether free will is absolute. The purpose of this article is the legal justification that free will is absolute. To substantiate this thesis, the author proposes to investigate two statements: 1. freedom of will is absolute, and legal norms specify it; 2. freedom of will is not absolute because regulations define its limits. The author examines absolute rights through the prism of their control in international treaties. In particular, an analysis of the normative consolidation and limitation of absolute rights in the International Covenant on Civil and Political Rights, the Convention on the Protection of Human Rights and Fundamental Freedoms, and the Canadian Charter of Rights and Freedoms was carried out. The author analyses the legal grounds for limiting absolute rights. The scientist concludes that the definition of a specific right as absolute is more connected not with the prohibition to limit it but with its significant meaning. It instead characterises absolute rights as natural and inalienable, although not all absolute rights are. The author claims that free will can be considered an absolute right from which other rights arise. The researcher cites an analogy when the absolute right to life gives rise to the right to health care, which gives rise to a whole series of patient rights. As a result, the author emphasises the possibility of assuming that free will is one of the absolute rights from which all others derive. At the same time, it is noted that the possibility of defining freedom of will as a personal non-property right or a principle of law requires a separate study.